Previous Early Antenatal Service Utilization Improves Timely Booking: Cross-Sectional Study at University of Gondar Hospital, Northwest Ethiopia - Tadesse Belayneh; Mulat Adefris; Gashaw Andargie (Journal of Pregnancy)
Background. Early booking of antenatal care (ANC) is regarded as a cornerstone of maternal and neonatal health care. However, existing evidence from developing countries indicate that lots of pregnant woman begin ANC booking lately. Objective. It was aimed to assess timing of ANC booking and associated factors among pregnant women attending ANC clinic at University of Gondar Hospital, 2013. Methods. An institution based cross-sectional study design was used to collect data with a face-to-face interview technique. Bivariate and multivariate analysis was used to identify associated factors for early ANC visit using SPSS version 20. Results. From total women (N = 369) interviewed, 47.4% were timely booked. Mothers with younger age (AOR = 3.83, 95% CI: 1.89, 10.53), formal education (AOR = 1.06, 95% CI: 1.03, −7.61), previous early ANC visit (AOR = 2.39, 95% CI: 2.23, 9.86), and perceived ANC visit per pregnancy of four and greater were significantly associated with early ANC visit. Conclusions. Although late booking is a problem in this study, previous early utilization of ANC visit favors current timely booking. This indicates that the importance of early booking was appropriately addressed from previous visits. Counseling of timely booking during ANC visit should be strengthened. Moreover, empowering through education is also recommended.